2016
DOI: 10.1152/physiolgenomics.00089.2016
|View full text |Cite
|
Sign up to set email alerts
|

Microbial short chain fatty acid metabolites lower blood pressure via endothelial G protein-coupled receptor 41

Abstract: Short chain fatty acid (SCFA) metabolites are byproducts of gut microbial metabolism that are known to affect host physiology via host G protein-coupled receptor (GPCRs). We previously showed that an acute SCFA bolus decreases blood pressure (BP) in anesthetized mice, an effect mediated primarily via Gpr41. In this study, our aims were to identify the cellular localization of Gpr41 and to determine its role in BP regulation. We localized Gpr41 to the vascular endothelium using RT-PCR: Gpr41 is detected in inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
269
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(282 citation statements)
references
References 47 publications
3
269
2
8
Order By: Relevance
“…Hence, a growing body of evidence supports that a high blood pressure (BP) is coupled to depressed carbohydrate fermentation [50]. Prescient ex vivo studies using pressure myography applied to rodent and human samples suggested that SCFA induce the vasodilation of resistance vessels in an endothelium-dependent manner [53][54][55]. Binding of SCFAs to the GPCR can activate a variety of intracellular signaling cascades, involving nuclear transcription, enzyme activation, and cell membrane ion transport [56].…”
Section: Role Of Decreased Carbohydrate Fermentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, a growing body of evidence supports that a high blood pressure (BP) is coupled to depressed carbohydrate fermentation [50]. Prescient ex vivo studies using pressure myography applied to rodent and human samples suggested that SCFA induce the vasodilation of resistance vessels in an endothelium-dependent manner [53][54][55]. Binding of SCFAs to the GPCR can activate a variety of intracellular signaling cascades, involving nuclear transcription, enzyme activation, and cell membrane ion transport [56].…”
Section: Role Of Decreased Carbohydrate Fermentationmentioning
confidence: 99%
“…At the mRNA level, Gpr41 is expressed in the vascular endothelium of intact vessels, where it lowers baseline BP by decreasing active vascular tone [54]. Gpr41-null mice present with hypertension of vascular origin: at baseline, plasma renin concentration is similar in Gpr41 KO and WT mice, and the systolic hypertension in Gpr41 KO mice is not salt-sensitive [54].…”
Section: Role Of Decreased Carbohydrate Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal microbial community is especially vital to metabolic homeostasis as it participates in nutrient absorption and maintaining the health of the intestinal tract. Specifically, intestinal microbiota aid in the production of bioactive compounds and some essential nutrients and metabolites and, arguably their most beneficial role within the intestinal environment, generate short chain fatty acids (SCFA) (Natarajan and Pluznick 2015). Although pathogenic bacteria are also present, within normal/healthy hosts diseased/inflammatory states are efficiently regulated and do not negatively alter metabolism.…”
Section: Nutrients and The Regulation Of Metabolic Homeostasismentioning
confidence: 99%
“…The genetic deletion of either FFAR2 or FFAR3 expression in mice was found to either exacerbate or reduce a number of inflammatory diseases. Studies have implicated FFAR2 in diabetes (3), obesity (49), colitis (1016), colon cancer (17), and arthritis (10); FFAR3 has been implicated in diabetes (3), colitis (14), hypertension (18), and asthma (19). …”
mentioning
confidence: 99%